O contrato de trabalho da pessoa com deficiência no ordenamento jurídico pátrio: inclusão social e acessibilidade - Silva, Matheus de Lima (Universidade Federal do Tocantins, 2021)
This research seeks to analyze the employment contract of people with disabilities - PwD, as to their guarantees of social inclusion and accessibility for the good performance of their functions as a job. In this context, the following problem arises: What legal aspects are related to the employment contract of people with disabilities in the Brazilian legal system? From bibliographical references, articles and legislation that address the structuring of the contract and the profile of the PCD, available through searches in official electronic addresses and in recognized scientific journals, such as the Federal Government website (Planalto) and websites electronics of the higher courts. This study is predominantly descriptive, but will contain an explanatory dimension. It will be of basic and applied nature, with a quali-quantitative approach, and will be carried out from bibliographical and documentary research, through the deductive method. At the end of this research work, an answer to the problem is possible, building some reflections on the inclusion of people with disabilities in the labor market.